2022
DOI: 10.1002/advs.202200033
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of the Peripheral Immune Response Induced by Local Microwave Ablation in Patients with Breast Cancer

Abstract: Minimally invasive thermal therapies have been attempted in the treatment of breast cancer, and the immune response induced by these therapies has not been fully reported. A clinical trial is performed to determine the effect of microwave ablation (MWA) in the treatment of early‐stage breast cancer. The authors perform single‐cell RNA sequencing on peripheral blood mononuclear cells (PBMCs) from six patients before and after ablation. NK and CD8+T cells are activated by MWA of breast cancer, with the increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 54 publications
0
25
1
Order By: Relevance
“…Therefore, the influencing factors for ablation combine therapy are more complex, including the optimal timing of immunotherapy, the choice of adjuvant immunotherapy, and application order of ablation and immunotherapy ( 101 ). Previous study indicated that ICIs treatment after MWA, PBMCs showed higher T-cell activity than that of pre-MWA treatment ( 102 ). Besides, Imiquimod treatment after cryoablation resulted in better tumor clearance (10/10 vs 3/7 tumors; p =0.0147) and overall treatment efficacy (9/10 vs 2/7 relapse-free tumors; p =0.0345) than immunotherapy before cryoablation in basal cell carcinoma according to Georgios Gaitanis et al ( 103 ).…”
Section: Challenges For Combining Ablation and Immunotherapymentioning
confidence: 91%
“…Therefore, the influencing factors for ablation combine therapy are more complex, including the optimal timing of immunotherapy, the choice of adjuvant immunotherapy, and application order of ablation and immunotherapy ( 101 ). Previous study indicated that ICIs treatment after MWA, PBMCs showed higher T-cell activity than that of pre-MWA treatment ( 102 ). Besides, Imiquimod treatment after cryoablation resulted in better tumor clearance (10/10 vs 3/7 tumors; p =0.0147) and overall treatment efficacy (9/10 vs 2/7 relapse-free tumors; p =0.0345) than immunotherapy before cryoablation in basal cell carcinoma according to Georgios Gaitanis et al ( 103 ).…”
Section: Challenges For Combining Ablation and Immunotherapymentioning
confidence: 91%
“…Macroscopically, MWA treatment was found to induce systemic immune responses and confirmed that B cells played an important role in MWA‐activated immune responses. [ 149 ]…”
Section: Clinical Physiotherapy‐activated or Combined Immunotherapymentioning
confidence: 99%
“…Macroscopically, MWA treatment was found to induce systemic immune responses and confirmed that B cells played an important role in MWA-activated immune responses. [149] The relationship between the specific immune response and T-cell response and tumor treatment outcome was analyzed in the study conducted by Katharina et al who traced and assayed their levels in the peripheral blood of patients with liver cancer after MWA. [150] Several results were obtained, for example, 1) The TAAs for specifically activating T cell responses were enhanced after MWA.…”
Section: Mwa-activated Immune Responsesmentioning
confidence: 99%
“…Similarly, a couple of studies have been proposed to combine HIFU with immunotherapy. The advantages of such combination can be concluded as: (1) Thermal therapy induced increase of IFN- , HSP 27, HSP 70 concentrations and decrease of IL-10, IL-4, TGFb-1, and TGFb-2 concentrations to help improve the antigen-presenting capability [ 16 , 103 , 104 ]; (2) Combined treatments also resulted in increased concentrations of dendritic cells and decreased concentrations of IL-10 and CD4 Foxp3 , leading to more efficient priming and activation of T-cells [ 13 , 105 ]; (3) Combined therapy induced elevated long-term memory markers CD4 CD44 CD62 and CD8 CD44 CD62 for prevention of tumor recurrence and thus enhanced sensitization of ICIs therapy [ 106 ]. In addition, the mechanical effect of HIFU also plays a significant part in improving the anti-tumor immune response, as the addition of the microbubbles was found to have induced the Th1 reaction to strengthen the activity of DC and cytotoxic lymphocytes [ 107 ].…”
Section: Cancer Treatments Combined With Thermal Therapymentioning
confidence: 99%
“…Thermal damages include but are not limited to (1) cell membrane collapse, protein denaturation, mitochondrial dysfunction, halted enzyme function for over 50 °C, (2) inhibition of DNA replication, halted metabolism, the release of chemokines & cytokines for 41–45 °C, (3) release of pro-inflammatory cytokines, tumor antigens, RNA, DNA, heat shock proteins (HSPs) & high mobility group protein B1 (HMGB1) and so on. Besides, more evidence from recent studies indicates that thermal therapy could induce the immune response [ 12 , 13 , 14 , 15 , 16 , 17 ]. In tumor-draining lymph nodes (TDLN), thermal therapy can double the expression of CCL21 to make up for the reduced T cell homing [ 18 ].…”
Section: Introductionmentioning
confidence: 99%